المتفق والمختلف في القيم الأخلاقية بين اليهودية والمسيحية والإسلام: دراسة مقارنة - الديبو، إبراهيم أحمد (مركز فكر للدراسات والتطوير, 2021)
تناولت في بحثي الجانب الأخلاقي في اليهودية والمسيحية والإسلام، ويمكن أن ألخص أهم النقاط التي عرضها البحث: - إن التوراة الحالية اشتملت على وصايا أخلاقية تحض على الفضيلة وتنهى عن الرذيلة، وهي ما بقي من أثر الحق والوحي الذي جاء به الأنبياء. - نصوص التوراة والأسفار القديمة والتلمود تكشف عن كثير من أخلاق اليهود وصفاتهم القبيحة، ونظرتهم العنصرية والتعالي على كل الشعوب والأمم - من أخلاق اليهود التي ذكرها القرآن: الكذب والحسد واحتقار للآخرين، والظلم والخيانة، والغدر والفساد، وغير ذلك من أخلاق قبيحة، كان لها دور في سلوكهم السيئ وتفكيرهم المعوج. - إن المسيح عليه السلام جاء بقيم جديدة واجه بها الوعي اليهودي، فالمجتمع اليهودي كان مقوضا والأخلاق متدنية والعبادة اليهودية منحرفة ومتعصبة. - دعا المسيح عليه السلام إلى تغيير شامل في النفس الإنسانية يؤثر على السلوك الفردي والاجتماعي. - الإسلام يدعو إلى إحياء السلوك الأخلاقي الذي دعا إليه الأنبياء، وذكر لنا نماذج كثيرة من دعوى الأنبياء لأقوامهم وموقفهم من الانحرافات العقدية أو الأخلاقية. - إن علاقة المسلمين بالديانتين اليهودية والمسيحية علاقة تصديق وتصحح، تصدق ما بقي منهما، وتصحح ما طرأ عليها من إضافات أو تحريفات في جوانب العقيدة والأخلاق والتشريع -إن هدف القرآن من ذكر سير الأنبياء وقصصهم مع أقوامهم هو المحافظة على التراث الأخلاقي الذي ميز رسالات الأنبياء، وإتمام الصرح الإلهي الذي بناه الأنبياء على مر العصور.
In my research, I dealt with the ethical aspect of Judaism, Christianity and Islam, and I can summarize the most important points presented by the research: -The current Torah included moral commandments that encourage virtue and forbid immorality, and they are what remains of the traces of truth and revelation that were brought by the prophets. The texts of the Torah, the ancient books, and the Talmud reveal many of the Jews’ morals and ugly characteristics, and their racist view and condescension to all peoples and nations. -Among the manners of the Jews mentioned in the Qur’an: lying, envy, contempt for others, injustice and betrayal, treachery and corruption, and other ugly morals that played a role in their bad behavior and crooked thinking . -Christ, peace be upon him, brought new values with which he confronted the Jewish consciousness. The Jewish society was undermined, morals were low, and Jewish worship was perverted and intolerant. Christ, peace be upon him, called for a comprehensive change in the human soul that affects individual and social behavior -Islam calls for the revival of the moral behavior that the prophets called for, and it mentioned to us many examples of the prophets’ claim to their people and their position on doctrinal or moral deviations The relationship of Muslims to the Jewish and Christian religions is one of ratification of the remaining parts, and a correction of the changes and additions that have occurred to them in aspects of belief, morals and legislation. The goal of the Qur’an in mentioning the lives of the prophets and their stories with their people is to preserve the moral heritage that distinguished the messages of the prophets, but it has another message that is no less important and sacred, which is the completion of the divine edifice that the prophets built throughout the ages.
Keywords: القيم الأخلاقية -- العقيدة والأخلاق -- الأخلاق والأديان